Hollow CeO2 material, preparation method thereof and CeO2 modified diaphragm
By using hollow CeO2 material synthesized based on Cu2O template on the lithium-sulfur battery separator, the problem of polysulfide shuttle effect is solved, and the electrochemical performance and cycle stability of lithium-sulfur battery are significantly improved.
Patent Information
- Application Number
- CN202411388887.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
AI Technical Summary
The shuttle effect of polysulfides in existing lithium-sulfur batteries leads to an increase in the internal impedance of the battery and a decrease in electrochemical performance. The existing metal oxides are poor in the modification of the separator, making it difficult to effectively inhibit the diffusion of polysulfides.
Using Pearson's soft and hard acid-base theory based on Cu2O as the template, hollow CeO2 material was synthesized by sodium thiosulfate etchant, and hollow CeO2 material with excellent electrochemical performance was obtained through heat treatment, which was used to modify the lithium-sulfur battery separator to suppress multiple Shuttle effect of sulfide.
It realizes the simple and efficient preparation of hollow CeO2 materials with stable electrochemical properties, which significantly improves the rate performance, cycle performance and specific capacity of lithium-sulfur batteries, and extends the cycle life of the battery.
Smart Images

Figure CN119284937A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and is specifically a hollow CeO 2 Materials and preparation methods thereof and CeO 2 Modified diaphragm. Background Art
[0002] Among the existing energy storage systems, lithium-sulfur battery (Li-S) is a new type of energy storage system. The theoretical capacity of lithium-sulfur battery is as high as 1675mAh / g, and the theoretical mass energy density is as high as 2600Wh / kg. Moreover, elemental sulfur has abundant reserves, low cost, environmental friendliness, safety and reliability. Therefore, lithium-sulfur battery is considered to be the next generation of energy storage battery with great application prospects. However, there are still some bottleneck problems to be solved in the development of lithium-sulfur battery, including poor conductivity of positive electrode material S, shuttle effect of polysulfides (LiPSs), and volume expansion of electrodes during charging and discharging. Among them, the most serious and urgent problem to be solved is the "shuttle effect" of polysulfides. The elemental sulfur positive electrode forms soluble polysulfide intermediates during charging and discharging. The polysulfides diffuse in the electrolyte to the lithium negative electrode and continuously deposit on the surface of the lithium negative electrode, thereby increasing the internal impedance of the battery and sharply reducing the electrochemical performance. Therefore, inhibiting the shuttle effect of polysulfides has become the key to improving the comprehensive performance of Li-S batteries.
[0003] As an indispensable part of lithium-sulfur batteries, diaphragms play an important role in lithium-sulfur batteries. Existing lithium-sulfur batteries generally use single-layer polypropylene (PP) diaphragms. Since the pore size of PP diaphragms is much larger than the diameter of polysulfide molecules, it cannot hinder the diffusion of polysulfides inside the battery. Therefore, the diaphragm is usually optimized to inhibit the diffusion of polysulfides to the lithium negative electrode side, thereby improving the cycle life of the battery and increasing the coulombic efficiency of the battery. There are many ways to optimize the diaphragm. Adding an intermediate layer between the diaphragm and the battery, or forming a tightly connected functional material layer by growth, coating and filtration on the surface of the diaphragm is a more common diaphragm optimization method.
[0004] Hollow structure nanomaterials have a large specific surface area and pore volume. The large surface area indicates the presence of more active sites and the ability to fully contact the electrolyte, shorten the charge transfer distance, and accelerate the electrochemical reaction kinetics. The larger cavity can buffer the volume change of the electrode material during the electrochemical reaction and improve the cycle stability. They are mainly prepared by self-template method, soft template method and hard template method. Among them: the self-template method refers to the preparation of hollow structure micro-nano materials directly through electrochemical replacement method, Wald ripening mechanism or Kirkendall effect without the help of template. Although the self-template method has the advantages of simple method, low cost and high product purity, it has a narrow scope of application; the soft template method refers to the use of bubbles, droplets, macromolecular micelles, etc. as soft templates The method of synthesizing hollow structures by plate-based method, the hydrophobic end of the template is accumulated in the core of the micelle, while the hydrophilic end is accumulated on the surface of the micelle to adsorb the target substance, and the precursor is prepared by oxidation or polymerization of the target substance, and then the template is removed by high-temperature pyrolysis or solvent extraction to obtain hollow nanomaterials. It is easy to operate and the synthetic material has high morphological and dimensional quality, but a large amount of organic solvent is required to remove the template, and the template residue will affect the product performance; the hard template method is the most direct and effective method for synthesizing hollow micro-nanostructures, and its process mainly includes synthesizing hard templates, functionalizing or surface modifying hard templates, loading target substances or precursors on the templates, and removing hard templates. It is time-consuming, labor-intensive and costly, and when polymers are used as templates, the hollow structure is at risk of collapse.
[0005] Metal oxides usually contain oxygen anions (O 2- ), the material surface has strong polarity, which can effectively adsorb polysulfides by polar interaction, and the metal and O 2- There is a strong chemical reaction between them, which makes metal oxides insoluble in organic electrolytes and have good stability; moreover, compared with carbon materials, metal oxides provide sufficient adsorption sites to chemically anchor polysulfides; in addition, intrinsic defects and unique band structures make some metal oxides have good electrochemical properties, so they are expected to be widely used in modifying lithium-sulfur battery separators. However, the performance of existing metal oxides when used to modify lithium-sulfur battery separators is still poor.
[0006] In summary, how to prepare hollow structured metal oxides with stable electrochemical properties through a simpler and more efficient method, so as to effectively inhibit the "shuttle effect" of polysulfides in Li-S batteries, is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a hollow CeO 2 Materials and preparation methods thereof and CeO 2 The modified diaphragm is not only simple and efficient in preparation, but also has a good effect on the preparation of hollow CeO 2The material can effectively inhibit the "shuttle effect" of polysulfides and improve the electrochemical performance of lithium-sulfur batteries.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A hollow CeO 2 The method for preparing the material comprises the following steps:
[0010] Step 1: Dissolve 10-30 g of polyvinyl pyrrolidone in 600-800 mL of 50% ethanol solution, then add 300-500 mg of CeCl 3 7H 2 O, and then add 400-600 mg of Cu 2 O, at room temperature, stirred to obtain a brick red solution;
[0011] Step 2: First, 40-50 g of sodium thiosulfate was dissolved in 200 mL of deionized water to obtain a sodium thiosulfate solution, and then the sodium thiosulfate solution was added dropwise to the brick red solution to obtain a light yellow solution. The solution was stirred at room temperature, and then allowed to stand for aging, centrifuged, washed and vacuum dried in sequence to obtain a light yellow hollow CeO 2 powder;
[0012] Step 3: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 300-400°C at a heating rate of 2°C / min in an air atmosphere and kept at this temperature for 2-4 hours to obtain a highly crystalline hollow CeO 2 Material.
[0013] Furthermore, the Cu in step 1 2 O was prepared by the following method:
[0014] Step 1.1, mixing ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution;
[0015] Step 1.2: In a water bath at 50-80°C, first add 1-4 g of Cu 2 SO 4 ·5H 2 O was dissolved in 100-300 mL of the ethanol solution prepared in step 1.1, and then 10-30 mL of ethylene glycol was added, stirred for 40 min, and then 5-20 mL of 2M NaOH solution was added dropwise, stirred for 40 min, to obtain a black solution;
[0016] Step 1.3, add 3-10 g of ascorbic acid powder into 30-50 mL of ultrapure water and stir for 40 min to obtain an ascorbic acid solution;
[0017] Step 1.4, add ascorbic acid solution dropwise to the black solution to obtain a brick-red solution, stir at room temperature for 40 min, then let stand for 3 h, then filter, wash and vacuum dry in sequence to obtain a brick-red Cu 2 O.
[0018] Furthermore, the stirring in step 1 is carried out using a magnetic stirrer for 30 minutes.
[0019] Furthermore, the stirring time of step 2 is 1 h.
[0020] Furthermore, the static aging time in step 2 is 12 hours.
[0021] Furthermore, the washing in step 2 is performed by alternately washing with deionized water and anhydrous ethanol for 3 times.
[0022] Furthermore, the vacuum drying in step 2 is performed in a vacuum drying oven at 60° C. for 12 hours.
[0023] A hollow CeO 2 Material.
[0024] A CeO 2 Modified membrane, including commercial polypropylene membrane, the surface of commercial polypropylene membrane base is coated with hollow CeO 2 Material.
[0025] Furthermore, the CeO 2 The modified diaphragm is prepared by the following method:
[0026] Weigh the hollow CeO according to the mass ratio of 8:1:1 2 After the material, acetylene black and PVDF were mixed and ground, NMP was added dropwise and stirred to obtain a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator for Li-S batteries and dried to obtain CeO 2 Modified diaphragm.
[0027] Compared with the prior art, the present invention has the following technical effects:
[0028] The present invention is based on Pearson's hard and soft acid-base theory. 2 O as template, with sodium thiosulfate Na 2 S 2 O 3 As an etchant, a hollow structure of cerium oxide CeO was synthesized. 2 During the reaction, Cu 2O and the corresponding reaction products not only have no effect on the hollow structure of cerium oxide, but also do not need to remove the template in the later stage, avoiding the potential problems of the traditional template method for preparing hollow structure nanomaterials. Then, hollow CeO with excellent electrochemical performance and stable structure is obtained by heat treatment. 2 Materials, throughout the entire preparation process, the raw materials used are non-toxic, harmless, and pollution-free, and the preparation process is simple, the production cycle is short, and it is more efficient and feasible.
[0029] The hollow CeO prepared by the present invention 2 The material has the advantages of trivalent and tetravalent oxidation states and reversible surface oxygen ion exchange, and has excellent catalytic performance. 2 After being stimulated by heat, light and electricity in the external environment, the outer electrons of the atoms or ions in the nucleus break free from the constraints of the nucleus and become free electrons. Vacancies are formed at the corresponding positions, making the crystal defective due to the existence of free electrons and holes, that is, charge defects. In charge defects, free electrons are negatively charged and holes are positively charged. In the redox process of lithium-sulfur batteries, the polysulfide ions generated in the polysulfide are CeO 2 The positively charged holes formed by the crystals are adsorbed, that is, polar adsorption is produced, thereby inhibiting the "shuttle effect" of polysulfides. Therefore, using it to modify commercial lithium-sulfur battery separators can give Li-S batteries better rate performance, cycle performance and higher specific capacity, thereby improving the electrochemical performance of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Synthesis of CeO in Example 1 of the present invention 2 XRD pattern of
[0031] Figure 2 Synthesis of CeO in Example 1 of the present invention 2 SEM images of
[0032] Figure 3 Synthesis of CeO in Example 1 of the present invention 2 Surface SEM image of the modified diaphragm;
[0033] Figure 4 Synthesis of CeO in Example 1 of the present invention 2 The charge and discharge curves of Li-S batteries assembled with modified separators and commercial separators at a current density of 0.1C;
[0034] Figure 5 Synthesis of CeO in Example 1 of the present invention 2 The Li-S battery assembled with modified separator has a current density of 0.1-0.5 mV s -1 CV curve at a rate of;
[0035] Figure 6 Synthesis of CeO in Example 1 of the present invention 2 Comparison of rate performance of Li-S batteries assembled with modified separators and commercial separators;
[0036] Figure 7 Synthesis of CeO in Example 1 of the present invention 2 Comparison of the cycling performance of Li-S batteries assembled with modified separators and commercial separators at a current density of 0.2C;
[0037] Figure 8 Synthesis of CeO in Example 1 of the present invention 2 Comparison of the cycling performance of Li-S batteries assembled with modified separators and commercial separators at 1C current density. DETAILED DESCRIPTION
[0038] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0039] Example 1
[0040] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; first, in a water bath at 70°C, add 2 g of Cu 2 SO 4 ·5H 2 O was dissolved in 240 mL of ethanol solution, and then 20 mL of ethylene glycol was added, stirred for 40 min, and then 10 mL of 2 M NaOH solution was added dropwise, stirred for 40 min to obtain a black solution; 6 g of ascorbic acid powder was added to 30 mL of ultrapure water, stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0041] Step 2: Dissolve 20 g of polyvinylpyrrolidone (PVP) in 600 mL of 50% ethanol solution, then add 400 mg of CeCl 3 7H 2 O, and then add 500 mg of Cu 2 O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0042] Step 3: First, 50 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0043] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 400°C at a heating rate of 2°C / min in an air atmosphere for 2 h to obtain a highly crystalline hollow CeO 2 Material.
[0044] like Figure 1 As shown in the figure, the XRD pattern has sharp diffraction peaks, indicating that the hollow CeO prepared in Example 1 2 The material samples have good crystallinity.
[0045] like Figure 2 As shown, the hollow CeO prepared in Example 1 2 The material is a hollow structured sphere with a regular shape and a particle size of about 600nm, and the size is relatively uniform.
[0046] Example 2
[0047] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; in a water bath at 70°C, first add 1.5 g of Cu 2 SO 4 ·5H 2 O was dissolved in 100 mL of ethanol solution, and then 10 mL of ethylene glycol was added, stirred for 40 min, and then 5 mL of 2 M NaOH solution was added dropwise, stirred for 40 min, to obtain a black solution; 3 g of ascorbic acid powder was added to 30 mL of ultrapure water, stirred for 40 min, to obtain an ascorbic acid solution; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0048] Step 2: Dissolve 20 g of polyvinyl pyrrolidone (PVP) in 600 mL of 50% ethanol solution, then add 300 mg of CeCl 3 7H 2 O, and then add 400 mg of Cu 2O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0049] Step 3: First, 40 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0050] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 300°C at a heating rate of 2°C / min in an air atmosphere for 4 h to obtain a highly crystalline hollow CeO 2 Material.
[0051] Example 3
[0052] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; in a water bath at 80°C, first add 2.5 g of Cu 2 SO 4 ·5H 2 O was dissolved in 200 mL of ethanol solution, and then 15 mL of ethylene glycol was added, stirred for 40 min, and then 7.5 mL of 2 M NaOH solution was added dropwise, stirred for 40 min, and a black solution was obtained; 5 g of ascorbic acid powder was added to 40 mL of ultrapure water, stirred for 40 min, and an ascorbic acid solution was obtained; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, which was stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0053] Step 2: Dissolve 30 g of polyvinyl pyrrolidone (PVP) in 600 mL of 50% ethanol solution, then add 300 mg of CeCl 3 7H 2 O, and then add 400 mg of Cu 2 O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0054] Step 3: First, 50 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0055] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 300°C at a heating rate of 2°C / min in an air atmosphere for 2 h to obtain a highly crystalline hollow CeO 2 Material.
[0056] Example 4
[0057] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; in a water bath at 60°C, firstly, 2 SO 4 ·5H 2 O was dissolved in 100 mL of ethanol solution, and then 10 mL of ethylene glycol was added, stirred for 40 min, and then 10 mL of 2 M NaOH solution was added dropwise, stirred for 40 min to obtain a black solution; 8 g of ascorbic acid powder was added to 30 mL of ultrapure water, stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0058] Step 2: Dissolve 20 g of polyvinyl pyrrolidone (PVP) in 700 mL of 50% ethanol solution, then add 300 mg of CeCl 3 7H 2 O, and then add 400 mg of Cu 2 O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0059] Step 3: First, 40 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0060] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 350°C at a heating rate of 2°C / min in an air atmosphere for 4 h to obtain a highly crystalline hollow CeO 2 Material.
[0061] Example 5
[0062] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; first, in a water bath at 60°C, add 3 g of Cu 2 SO 4 ·5H 2 O was dissolved in 200 mL of ethanol solution, and then 20 mL of ethylene glycol was added, stirred for 40 min, and then 15 mL of 2 M NaOH solution was added dropwise, stirred for 40 min to obtain a black solution; 10 g of ascorbic acid powder was added to 40 mL of ultrapure water, stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0063] Step 2: Dissolve 20 g of polyvinylpyrrolidone (PVP) in 700 mL of 50% ethanol solution, then add 400 mg of CeCl 3 7H 2 O, and then add 500 mg of Cu 2 O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0064] Step 3: First, 45 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0065] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 300°C at a heating rate of 2°C / min in an air atmosphere for 2 h to obtain a highly crystalline hollow CeO 2 Material.
[0066] Example 6
[0067] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; in a water bath at 70°C, first add 3.5 g of Cu 2 SO 4 ·5H 2 O was dissolved in 250 mL of ethanol solution, and then 30 mL of ethylene glycol was added, stirred for 40 min, and then 16 mL of 2 M NaOH solution was added dropwise, stirred for 40 min to obtain a black solution; 10 g of ascorbic acid powder was added to 45 mL of ultrapure water, stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0068] Step 2: Dissolve 20 g of polyvinylpyrrolidone (PVP) in 800 mL of 50% ethanol solution, then add 400 mg of CeCl 3 7H 2 O, and then add 500 mg of Cu 2 O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0069] Step 3: First, 50 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0070] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 400°C at a heating rate of 2°C / min in an air atmosphere for 3 h to obtain a highly crystalline hollow CeO 2 Material.
[0071] Example 7
[0072] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; first, in a water bath at 80°C, add 4 g of Cu 2 SO 4 ·5H 2O was dissolved in 300 mL of ethanol solution, and then 30 mL of ethylene glycol was added, stirred for 40 min, and then 18 mL of 2 M NaOH solution was added dropwise, stirred for 40 min to obtain a black solution; 9 g of ascorbic acid powder was added to 35 mL of ultrapure water, stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0073] Step 2: Dissolve 30 g of polyvinylpyrrolidone (PVP) in 700 mL of 50% ethanol solution, then add 400 mg of CeCl 3 7H 2 O, and then add 600 mg of Cu 2 O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0074] Step 3: First, 50 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0075] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 400°C at a heating rate of 2°C / min in an air atmosphere for 3 h to obtain a highly crystalline hollow CeO 2 Material.
[0076] Example 8
[0077] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; first, in a water bath at 60°C, add 1 g of Cu 2 SO 4 ·5H 2O was dissolved in 150 mL of ethanol solution, and then 15 mL of ethylene glycol was added, stirred for 40 min, and then 15 mL of 2 M NaOH solution was added dropwise, stirred for 40 min to obtain a black solution; 6 g of ascorbic acid powder was added to 50 mL of ultrapure water, stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0078] Step 2: Dissolve 30 g of polyvinylpyrrolidone (PVP) in 800 mL of 50% ethanol solution, then add 400 mg of CeCl 3 7H 2 O, and then add 500 mg of Cu 2 O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0079] Step 3: First, 40 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0080] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 350°C at a heating rate of 2°C / min in an air atmosphere for 3 h to obtain a highly crystalline hollow CeO 2 Material.
[0081] Example 9
[0082] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; in a water bath at 50°C, first add 2.5 g of Cu 2 SO 4 ·5H 2O was dissolved in 200 mL of ethanol solution, and then 20 mL of ethylene glycol was added, stirred for 40 min, and then 12.5 mL of 2 M NaOH solution was added dropwise, stirred for 40 min, and a black solution was obtained; 6.5 g of ascorbic acid powder was added to 45 mL of ultrapure water, stirred for 40 min, and an ascorbic acid solution was obtained; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, which was stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0083] Step 2: Dissolve 20 g of polyvinylpyrrolidone (PVP) in 700 mL of 50% ethanol solution, then add 400 mg of CeCl 3 7H 2 O, and then add 600 mg of Cu 2 O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0084] Step 3: First, 45 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0085] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 300°C at a heating rate of 2°C / min in an air atmosphere for 4 h to obtain a highly crystalline hollow CeO 2 Material.
[0086] Example 10
[0087] Step 1: Mix ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; first, in a water bath at 80°C, add 3 g of Cu 2 SO 4 ·5H 2O was dissolved in 250 mL of ethanol solution, and then 30 mL of ethylene glycol was added, stirred for 40 min, and then 20 mL of 2 M NaOH solution was added dropwise, stirred for 40 min to obtain a black solution; 10 g of ascorbic acid powder was added to 50 mL of ultrapure water, stirred for 40 min to obtain an ascorbic acid solution; the ascorbic acid solution was added dropwise to the black solution to obtain a brick-red solution, stirred for 40 min at room temperature, and then allowed to stand for 3 h, and then filtered, washed and vacuum dried in sequence to obtain a brick-red Cu 2 O;
[0088] Step 2: Dissolve 10 g of polyvinylpyrrolidone (PVP) in 600 mL of 50% ethanol solution, then add 500 mg of CeCl 3 7H 2 O, and then add 400 mg of Cu 2 O, stirred at room temperature with a magnetic stirrer for 30 min to obtain a brick-red solution;
[0089] Step 3: First, 45 g of sodium thiosulfate was dissolved in 200 mL of deionized water, and then the sodium thiosulfate solution was added dropwise to the brick-red solution. The solution gradually turned light yellow to obtain a light yellow solution. The solution was stirred at room temperature for 1 h, and then aged for 12 h. The solid was separated by centrifugation. The solid was then washed alternately with deionized water and anhydrous ethanol for 3 times, and finally placed in a vacuum drying oven at 60 ° C for 12 h to obtain a light yellow hollow CeO 2 powder;
[0090] Step 4: Hollow CeO 2 The powder was placed in a muffle furnace and heated from room temperature to 300°C at a heating rate of 2°C / min in an air atmosphere for 2 h to obtain a highly crystalline hollow CeO 2 Material.
[0091] Application Examples
[0092] The hollow CeO prepared in Example 1 was weighed according to the mass ratio of 8:1:1. 2 After the material, acetylene black and PVDF were mixed and ground, 10 drops of NMP were added and stirred to obtain a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator for Li-S batteries and dried to obtain CeO 2 Modified diaphragm.
[0093] like Figure 3 As shown, hollow CeO 2 The material is very evenly coated on the surface of commercial lithium-sulfur battery polypropylene separator.
[0094] MWCNTs / S was used as the positive electrode, metallic lithium was used as the negative electrode, and 1.0 M LiTFSI in DME:DOL=1:1Vol%with 1.0%LiNO 3 solution as electrolyte, with commercial polypropylene separator and CeO 2 The modified diaphragm was used as a lithium-sulfur battery diaphragm. The lithium-sulfur battery was assembled in a glove box filled with argon. The results of the electrochemical performance test are as follows:
[0095] like Figure 4 As shown, CeO 2 Compared with the lithium-sulfur battery assembled with the commercial polypropylene separator, the lithium-sulfur battery assembled with the modified separator has a smaller voltage hysteresis value (ΔE) and shows a relatively flat charge and discharge platform at 0.1C, proving that CeO 2 The modified diaphragm can bind polysulfides to the positive electrode side, reducing the negative impact of the shuttle effect. At the same time, it reduces the polarization rate of battery charging and discharging and increases the battery capacity.
[0096] like Figure 5 As shown, CeO 2 The lithium-sulfur battery assembled with the modified diaphragm has a higher current density and a larger peak area. When the scan rate increases, the voltage and response current of the reduction peak decrease, the voltage and response current of the oxidation peak increase, and the peak position shifts significantly, indicating that CeO 2 It can alleviate polarization and promote the redox kinetics of polysulfide reactions.
[0097] The LAND CT 2001A battery test system was used to test CeO 2 The rate performance and 0.2C and 1C cycle performance of Li-S batteries assembled with modified separators at different current densities, as well as the rate performance and 0.2C cycle performance of Li-S batteries assembled with polypropylene separators at different current densities, such as Figure 6 , Figure 7 and Figure 8 As shown, CeO 2 The rate performance of the Li-S battery assembled with the modified separator is even better. When the current density is 0.1C, the initial discharge capacity is 1370mAh g -1 ; At 0.2C current density, the first discharge capacity is 1135.2mAh g -1 After 100 cycles, the capacity is 752.9 mAh g -1 ; The first discharge capacity at 1C current density is 1067.4mAh g -1 After 100 cycles, the capacity is 519.2 mAh g -1 , with a higher capacity retention rate.
Claims
1. A method for preparing a hollow CeO2 material, characterized in that: The steps include: Step 1: Dissolve 10-30 g of polyvinyl pyrrolidone in 600-800 mL of 50% ethanol solution, add 300-500 mg of CeCl3·7H2O, and after it is dissolved, add 400-600 mg of Cu2O, stir at room temperature, and obtain a brick red solution; Step 2: First, dissolve 40-50 g of sodium thiosulfate in 200 mL of deionized water, and then add the sodium thiosulfate solution dropwise into the brick-red solution to obtain a light yellow solution. Stir at room temperature, then stand for aging, centrifuge, wash and vacuum dry in sequence to obtain a light yellow hollow CeO2 powder. Step 3: Place the hollow CeO2 powder in a muffle furnace, and heat it from room temperature to 300-400°C at a heating rate of 2°C / min in an air atmosphere, and keep it warm for 2-4 hours to obtain a highly crystalline hollow CeO2 material.
2. The method for preparing the hollow CeO2 material according to claim 1, characterized in that: The Cu2O in step 1 is prepared by the following method: Step 1.1, mixing ultrapure water and anhydrous ethanol in a volume ratio of 2:1 to obtain an ethanol solution; Step 1.2, in a water bath at 50-80°C, first dissolve 1-4 g of Cu2SO4·5H2O in 100-300 mL of the ethanol solution prepared in step 1.1, then add 10-30 mL of ethylene glycol, stir for 40 min, then add 5-20 mL of 2M NaOH solution dropwise, stir for 40 min, to obtain a black solution; Step 1.3, add 3-10 g of ascorbic acid powder into 30-50 mL of ultrapure water and stir for 40 min to obtain an ascorbic acid solution; Step 1.4: Add ascorbic acid solution dropwise to the black solution to obtain a brick-red solution. Stir the solution at room temperature for 40 min, let it stand for 3 h, and then filter, wash and vacuum dry in sequence to obtain brick-red Cu2O.
3. The method for preparing the hollow CeO2 material according to claim 1, characterized in that: The stirring in step 1 is carried out by using a magnetic stirrer for 30 minutes.
4. The method for preparing the hollow CeO2 material according to claim 1, characterized in that: The stirring time of step 2 is 1 h.
5. The method for preparing the hollow CeO2 material according to claim 1, characterized in that: The standing aging time in step 2 is 12 hours.
6. The method for preparing the hollow CeO2 material according to claim 1, characterized in that: The washing in step 2 is performed by alternately washing with deionized water and anhydrous ethanol for 3 times.
7. The method for preparing the hollow CeO2 material according to claim 1, characterized in that: The vacuum drying in step 2 is carried out in a vacuum drying oven at 60° C. for 12 h.
8. A hollow CeO2 material prepared by the method as claimed in claim 1.
9. A CeO2 modified diaphragm, characterized in that: It comprises a commercial polypropylene separator, the surface of which is coated with the hollow CeO2 material as claimed in claim 8.
10. The CeO2 modified diaphragm according to claim 9, characterized in that: Prepared by the following method: The hollow CeO2 material, acetylene black and PVDF were weighed and mixed in a mass ratio of 8:1:1, and then NMP was added dropwise and stirred to obtain a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene diaphragm for a Li-S battery and dried to obtain a CeO2 modified diaphragm.